SINERGI GERAKAN PEDULI LINGKUNGAN MELALUI KULIAH KERJA NYATA (KKN) DI DESA KEDUNG PENGAWAS KECAMATAN BABELAN KABUPATEN BEKASI - Desti Purnama; Yoan Dira Putri, Alya Wahyudi, Purwaningtyas, Novia Rachma Shinta, Indriani Agustiningsih, Vina Pusp (JOURNAL OF COMMUNITY DEDICATION, 2026)
Community service through Real Work Lectures (KKN) represents a concrete form of student contribution in addressing environmental and social problems as an implementation of the Tri Dharma of Higher Education. This activity was carried out by Group 74 of Universitas Bhayangkara Jakarta Raya at Kedung Pengawas Village, Babelan District, Bekasi Regency, under the theme "Synergy of Environmental Care Movement to Realize a Clean, Healthy, and Comfortable Village". The implementation methods included field observation, direct socialization, participatory education, and community empowerment. The programs covered four main activities: (1) environmental-themed drawing and coloring for elementary school students; (2) environmental care, anti-bullying, and reproductive health education for elementary school students; (3) organic and inorganic waste sorting education and community-based waste sorting implementation; and (4) installation of environmental information boards at strategic village locations. The results showed a significant increase in environmental awareness and social understanding among the community through collaborative activities between students, village officials, and local residents.